Development of algebraic thinking: opportunities offered by the Swedish curriculum and elementary mathematics textbooks - Bråting, Kajsa; Madej, Lars; Hemmi, Kirsti (NOMAD Nordic Studies in Mathematics Education, 2019)
In search of the reasons for Swedish students’ low achievement in algebra in international and national evaluations, we investigate how the development of algebraic thinking is addressed in the Swedish national mathematics curriculum and two widely used mathematics textbook series for grades 1–6 in Sweden. The analytical tool used is based on the classification of ”big ideas” which research has shown as important for developing pupils’ algebraic understanding in early school grades. The results show that functional thinking, expressions, and equations are well represented topics both in the curriculum and the textbooks; however generalized arithmetic is a topic that is poorly developed in both the curriculum and the textbooks.